1985
DOI: 10.1128/aac.27.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of lactoperoxidase and myeloperoxidase against Bacillus cereus

Abstract: An oral periodontopathic bacterium, Bacillus cereus, was inhibited both by lactoperoxidase (LP) and myeloperoxidase (MP) antimicrobial systems. With the LP-SCN--H202 system, the growth inhibition was directly proportional to the amount of OSCN-ions present. The OSCN-, which is the principal oxidation product of the LP (or MP)-SCN--H202 system at neutral pH, is a normal component of human saliva. The oxidation products of both peroxidase systems inhibited the growth of the bacteria. This inhibition was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…This is compatible with the findings of Riley and Robertson (1984) who reported that activity of a granule-H202 combination against Brucella abortus was greatest at pH 5.5-6, but contrasts with the efficacy of a myeloperoxidase H202-halide system against Bacillus cereus at pH 6-8 (Tenovuo et al, 1985). However, when we compared S. aureus and E. coli at equivalent reagent concentrations in identical incubation conditions, E. coli was killed more rapidly and more completely than S. aureus, especially at pH 7.…”
Section: Discussionsupporting
confidence: 81%
“…This is compatible with the findings of Riley and Robertson (1984) who reported that activity of a granule-H202 combination against Brucella abortus was greatest at pH 5.5-6, but contrasts with the efficacy of a myeloperoxidase H202-halide system against Bacillus cereus at pH 6-8 (Tenovuo et al, 1985). However, when we compared S. aureus and E. coli at equivalent reagent concentrations in identical incubation conditions, E. coli was killed more rapidly and more completely than S. aureus, especially at pH 7.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, a computational model of LPO activity supported the concept that the effect of the measured decrease in SCN À transport on LPO enzymatic activity could not be compensated by upregulating either LPO or H 2 O 2 and thus predicted a loss of LPO-mediated host defense in CF airways. If the measured difference in apical SCN À between CF and non-CF airway epithelial cells is reflected in vivo, it is likely to be functionally significant since OSCN À production by LPO at the relevant SCN À concentrations are significantly different [33] and bacterial growth in vitro is inversely proportional to the [OSCN À ] [34]. Although certain changes in CF epithelial phenotype in culture have been noted by others, these changes were seen in primary cultures and disappeared after 6-11 days in culture [35].…”
Section: Discussionmentioning
confidence: 99%
“…The reaction mixture was prepared in an anaerobic environment because the reaction through GO required dissolved oxygen. The reaction mixture in 40 mM phosphate buffer (pH 7.7) was incubated at 37 uC for 10 and 30 min without the addition of bacteria, and the concentration of OSCN -was measured by monitoring the reaction with 5-thio-2-nitrobezoic acid (Tenovuo et al, 1985).…”
Section: Methodsmentioning
confidence: 99%